PENGARUH LABEL HALAL, DAN HARGA TERHADAP MINAT BELI PADA ICE CREAM MIXUE - Muhammad Sayyid Candivas (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2023)
Abstract. The purpose of this study was to determine the effect of Halal Labels and Prices on Interest in Buying Mixue Ice Cream at Mixue Stores, Kebumen Branch. The research method used is a quantitative descriptive approach with a total of 50 respondents. Data collection was carried out through an online questionnaire and the collected data was analyzed using SPSS software with a modified Likert scale. The results of the study show that the Halal Label and Price have a positive and significant effect on Purchase Intention, either partially or simultaneously.Keywords: Keywords: Halal Label, Price, Purchase Intention